1988
DOI: 10.1128/iai.56.4.880-884.1988
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a glucan-binding domain of glucosyltransferase (1,6-alpha-glucan synthase) from Streptococcus sobrinus

Abstract: A glucan-binding domain of 1,6-o-glucan synthase (dextransucrase) (GTF-S) was isolated from a trypsin digest of the Streptococcus sobrinus enzyme. The large 60.5-kilodalton peptide had an affinity for dextran comparable to that of the native enzyme, but had no glucan synthesis activity. The domain was produced in high yield compared with other large cleavage products, which allowed easy purification by size exclusion high-pressure liquid chromatography and affinity chromatography. Two other proteases (mouse su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 24 publications
1
48
0
1
Order By: Relevance
“…mutans Dex (Igarashi et al 1995), was necessary for dextran-binding ability. As glucan-binding proteins, such as Gtfs, Gbp and Dei, possess A and C repeats in glucanbinding sites (Ferretti et al 1987;Mooser and Wong 1988;Russell et al 1988;Banas et al 1990;Sun et al 1994), it was expected that the Dex, one of the glucan-binding proteins, would also have similar sequences. However, the expected sequences have not been detected in the Dex, implying that the binding mode of Dex to dextran is different from that of Gtfs, Gbp and Dei.…”
Section: Discussionmentioning
confidence: 99%
“…mutans Dex (Igarashi et al 1995), was necessary for dextran-binding ability. As glucan-binding proteins, such as Gtfs, Gbp and Dei, possess A and C repeats in glucanbinding sites (Ferretti et al 1987;Mooser and Wong 1988;Russell et al 1988;Banas et al 1990;Sun et al 1994), it was expected that the Dex, one of the glucan-binding proteins, would also have similar sequences. However, the expected sequences have not been detected in the Dex, implying that the binding mode of Dex to dextran is different from that of Gtfs, Gbp and Dei.…”
Section: Discussionmentioning
confidence: 99%
“…Truncation of the C‐terminal end conducted to suppress glucan binding abilities of GTF‐I [21]. Mooser and Wong [88]as well as Kobayashi et al [89]have isolated by mild trypsic digestion of S. sobrinus GTF‐S and GTF‐I, peptides of 60.5 or 55 kDa, respectively, having the same affinity for glucan as native enzyme, but displaying no activity. Sequencing of peptides from GTF‐I of S. sobrinus showed that it corresponded to the C‐terminal part.…”
Section: Structural and Functional Organisation Of The Glucansucrasesmentioning
confidence: 99%
“…The decreased enzyme activity resulting from loss of direct repeats has been seen in other GTF enzymes (1,5,19) as well as in related pneumococcal enzymes with similar direct repeats (8). These decreased activities are thought to be due to decreased ability of the enzymes to bind their substrate (8,22). The results presented here show that the deletion of three internal direct repeats in strain CH107 did not decrease the amounts of cell-associated or extracellular GTF antibody-reactive protein, confirming that the decreased activities seen were due to a qualitative change in the enzyme.…”
Section: Discussionmentioning
confidence: 95%
“…gtfG encodes a series of six direct repeats in the carboxyl-terminal region. These conserved repeats, which in one classification system have been designated A, B, C, and D based on their similarity to consensus sequences (1,5,10,11), are thought to function in glucan binding (5,22), and are similar to ligand binding domains of proteins found in other gram-positive bacteria (34,36).…”
mentioning
confidence: 99%